2009
DOI: 10.1088/0957-4484/20/20/204027
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and hydrogen storage properties of a MgH2incorporated carbon aerogel scaffold

Abstract: A new approach to the incorporation of MgH2 in the nanometer-sized pores of a carbon aerogel scaffold was developed, by infiltrating the aerogel with a solution of dibutylmagnesium (MgBu2) precursor, and then hydrogenating the incorporated MgBu2 to MgH2. The resulting impregnated material showed broad x-ray diffraction peaks of MgH2. The incorporated MgH2 was not visible using a transmission electron microscope, which indicated that the incorporated hydride was nanosized and confined in the nanoporous structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
122
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(123 citation statements)
references
References 34 publications
1
122
0
Order By: Relevance
“…Scaffolding, a technique relatively new to the field of hydrogen storage, involves the deposition of a storage material within the (nano-sized) pores of a host scaffold material. 76,77 High-throughput materials screening, a promising technique commonly used in the pharmaceutical industry, couples the steps of synthesis, processing, and characterization to accelerate the discovery of hydrogen storage materials. 78,79 V. Materials attributes and methods for their evaluation…”
Section: Chemical Hydridesmentioning
confidence: 99%
“…Scaffolding, a technique relatively new to the field of hydrogen storage, involves the deposition of a storage material within the (nano-sized) pores of a host scaffold material. 76,77 High-throughput materials screening, a promising technique commonly used in the pharmaceutical industry, couples the steps of synthesis, processing, and characterization to accelerate the discovery of hydrogen storage materials. 78,79 V. Materials attributes and methods for their evaluation…”
Section: Chemical Hydridesmentioning
confidence: 99%
“…Work by Vajo and co-workers [24,25] in the MHCoE shows that nanoconfinement can lead to dramatic (~509) increases in hydrogen release rates. However, a synthetic difficulty is finding a way to introduce the complex metal hydride into the nanoscaffold.…”
Section: B Nanoconfinementmentioning
confidence: 99%
“…However, a synthetic difficulty is finding a way to introduce the complex metal hydride into the nanoscaffold. A significant breakthrough [25] in nanoconfinement came from the organometallic synthesis methods developed by Jensen and co-workers at the University of Hawaii (UH). The original syntheses [21] of nanoconfined LiBH 4 required infusing the carbon aerogel with liquid (i.e., melted) LiBH 4 .…”
Section: B Nanoconfinementmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Indeed, it has been reported that the desorption temperature T d can be decreased to 85 and 115°C compared to T d Ͼ 350°C for bulk Mg. 11,12 Nanoconfinement of MgH 2 nanoparticles incorporated in carbon aerogel scaffold prohibits nanoparticles to coarsen and leads to increased number of hydrogenation/dehydrogenation cycles and with faster dehydrogenation kinetics compared to the ball milled nanostructured materials. 15,16 However, so far, insufficient attention has been paid to the thermal stability of Mg nanoparticles. Moreover, knowledge and understanding of the structural evolution of Mg nanoparticles during hydrogenation is lacking.…”
Section: Introductionmentioning
confidence: 99%